Knowledge Management Portal for Retaining Organizational Critical Knowledge - Kumaravel, Sivasangoo (2010)
Knowledge Management (KM) is widely being accepted by many corporations. Large corporations like Siemens and Petronas have implemented their projects earlier realizing the importance of it. Main reason of implementing KM is it can retain & improve knowledge and skill in the organization. By implementing KM, it can help companies make better products in term of innovation and subsequently they can compete better in market (sustainability). This report discusses the background of KM and some success story about how companies have benefited fiom the project. The report also discusses how KM portal can be implemented in SMT Technologies (SMTT) with the belief of KM implementation can help the organization to retain critical knowledge/skill. This will help SMTT to overcome the problem of high rate of employee turnover. The portal is well accepted by the organization and will be implemented to manage the organization's knowledge.